Enhancing member engagement in a Tier 3 personality disorder service during COVID-19: evaluation of a virtual group programme. Issue 6 (9th November 2022) - Smith, Emma; Papastavrou Brooks, Cat; Clifford, Emma; Giles, Emily; Dring, Jessica; Startup, Helen
Abstract: Background: Drop-out rates from evidence-based interventions for people with a diagnosis of personality disorder (PD) are high. The COVID-19 pandemic has likely exacerbated barriers to engagement with the introduction of virtual working. Virtual therapy has a good evidence-base for Axis I disorders, but limited research for Axis II disorders. Aims: To investigate facilitators and barriers to engagement in a Tier 3 PD service virtual group programme. Method: A virtual group programme was developed in collaboration with service members, and analysed members' attendance rates over a 5-month period pre- and post-COVID-19. Thematic analysis of semi-structured telephone interviews with 38 members is reported, describing their experience of the virtual group programme. Results: Attendance rates were significantly higher pre-COVID (72%) than post-COVID (50%). Thematic analysis highlighted key barriers to attendance were: practical issues, low motivation, challenges of working in a group online and feeling triggered at home. Main promoters of engagement were: feeling valued, continued sense of connection and maintaining focus on recovery. Discussion: The results suggest that the pandemic has exacerbated relational and practical barriers to engagement in a Tier 3 PD service. Ways of enhancing engagement are discussed, as well as preliminary recommendation for services offering virtual therapy to people with a diagnosis of PD.